Simple Approach in Measuring the Synthesized Zeolite from Kaolin as Nutrient Retention for Mung Bean Growth - Azhar, Faiz Hafeez; Norsuhailizah Sazali; Zawati Harun; Mohan Raj A/L Paramasivam; Rosniza Hussin; Norazlianie Sazali; Riduan Jamalludin (Emerging Advances in Integrated Technology, 2023)
Since the 1960s, zeolites mesoporous structures have been employed in agriculture due to their efficiency as soil modifiers for plant growth that can retail minerals and important nutrients as well as cation exchange capacity (CEC). This characteristic is critical in ensuring that plant growth is not hampered by the elimination of minerals and nutrients from the fertilizer; thus, zeolite materials are always referred to as slow-release or slow retention of fertilizer. The purpose of this study is to evaluate the performance of kaolin-synthesized zeolites as controlled release fertilizers to reduce soil nutrient leaching. The zeolite Linde-type A used in this study was produced by hydrothermal synthesis from metakaolin clay (thermal treatment). This study's metakaolin clay was made through thermal treatment (calcination) of kaolin clay heated at 650 °C for 24 hours. X-ray diffraction (XRD) was used to determine that the phase of the synthesized zeolite was of the LTA type. Two experiments are conducted to examine the effects of zeolite on the trapping and sustaining of NPK fertilizer for plant growth. Compared to standard NPK fertilizers without zeolite, the fertilizer containing zeolite accelerated the growth of mung bean plants by 35.5% for stem height and 52.5% for leaf length. The mustard green plant grown with zeolite-integrated NPK fertilizer revealed a stem height difference of 37.5% and a leaf length difference of 10.3% compared to plants grown with standard NPK fertilizer without zeolite. This study indicated that zeolite has a strong capability for retaining minerals and nutrients, guaranteeing that plant growth is not inhibited by nutrient deficiency.